The consequences of primary cytomegalovirus infection in pregnancy. Issue 12 (December 1983) - Preece, P M; Blount, J M; Glover, J; Fletcher, G M; Peckham, C S; Griffiths, P D
Abstract : Altogether 54 children exposed prenatally to maternal cytomegalovirus (CMV) infection were followed up in a prospective study. Nine had congenital infection with CMV and 37 escaped congenital infection; in 8 congenital CMV could not be confirmed. The birthweight of children with congenital CMV was significantly lower than that of both controls and those who escaped congenital infection. Intrauterine infection was not clinically suspected in any of the children with congenital CMV, although two had head circumferences less than the third centile. Subsequently one child with congenital CMV developed marked psychomotor retardation, and one, in whom congenital CMV was not confirmed, showed mild developmental delay. Speech and language ability was significantly impaired in children with congenital CMV compared with controls and those who escaped congenital infection, suggesting that subtle damage may have occurred. The incidence of intrauterine transmission of CMV after exposure to infection in the first trimester was 20% and in the third trimester 40%, but no congenital infections resulted from exposure in the second trimester. The severity of congenital infection was not related to the time of exposure in utero. Our findings suggest that the risk to an individual fetus from maternal infection in early gestation is so low that termination of pregnancy cannot be recommended; screening of women for primary CMV infection in pregnancy seems therefore to have limited value.